2002
DOI: 10.1016/s0002-9343(02)01091-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency among free-living healthy young adults

Abstract: Long-term vitamin D insufficiency can cause secondary hyperparathyroidism and osteomalacia (1). In addition, there is increasing evidence that vitamin D may protect against common cancers, such as cancer of the colon (2-4), prostate (5), and breast (6). Young adults aged 17 to 35 years drink inadequate amounts of milk (7) and are concerned about exposure to the sun because of the fear of developing skin cancer (8,9), which increases the risk of vitamin D insufficiency (10). We sought to examine the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
343
4
12

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 573 publications
(384 citation statements)
references
References 19 publications
25
343
4
12
Order By: Relevance
“…Vitamin D insufficiency is not limited to elderly and osteoporotic patients. A study from Boston demonstrated that over two thirds of healthy young adults were vitamin D insufficient [19]. Using cross-sectional data from the Third National Health and Nutrition Examination Survey, we found that more than 92% of black and 61% of white Americans had vitamin D insufficiency defined by 25(OH)D less than 32 ng/mL.…”
Section: Prevalence Of Vitamin D Insufficiencymentioning
confidence: 86%
“…Vitamin D insufficiency is not limited to elderly and osteoporotic patients. A study from Boston demonstrated that over two thirds of healthy young adults were vitamin D insufficient [19]. Using cross-sectional data from the Third National Health and Nutrition Examination Survey, we found that more than 92% of black and 61% of white Americans had vitamin D insufficiency defined by 25(OH)D less than 32 ng/mL.…”
Section: Prevalence Of Vitamin D Insufficiencymentioning
confidence: 86%
“…Such studies are of particular importance among those living at higher latitudes where maintenance of sufficient vitamin D levels may be a problem given low UV exposure in wintertime (Tangpricha et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies have been carried out on postmenopausal women and elderly people owing to the greater risk of osteoporosis in these individuals. More recent studies have also reported low vitamin D status in younger adults, adolescents and children living at higher latitudes (Ala-Houhala et al, 1984;LambergAllardt et al, 1986;McKenna, 1992;Lehtonen-Veromaa et al, 1999;Fuleihan et al, 2001;Guillemant et al, 2001;Tangpricha et al, 2002;Ginty et al, 2004;Gordon et al, 2004). Given the role of vitamin D in bone mineralisation, vitamin D insufficiency is highly likely to have deleterious effects on bone mineral density (BMD) in this group, and thereby decreasing their ability to achieve their potential peak bone mass (Bonjour et al, 1994;Lehtonen-Veromaa et al, 2002a, b).…”
Section: Introductionmentioning
confidence: 99%
“…70 Vitamin D inadequacy constitutes a largely unrecognized epidemic in many populations worldwide [71][72][73] It has been reported in healthy children, 74 adolescents 75 and adults. 76,77 Vitamin D and prostate health Normal and malignant prostate cells contain VDRs, [78][79][80] which mediate the antiproliferative action of 1,25(OH)2D. 1,25(OH)2D, the biologically active form of vitamin D, binds to nuclear VDRs in the epithelial cells of the prostate.…”
Section: Hypovitaminosis Dmentioning
confidence: 99%